A Collaborative Governance in the Implementation of the Family Hope Program in Tilamuta District, Boalemo Regency - Makuta, Syahril; Nani, Yacob Noho; Tohopi, Rustam (PROVIDER JURNAL ILMU PEMERINTAHAN, 2025)
This research aims to find out and describe Collaborative Governance in the Implementation of the Family Hope Program in Tilamuta District, Boalemo Regency. Viewed from the Collaborative Process dimension: (a) Face to face dialogue, (b) Trust Building (building trust), (c) Commitment to process (commitment in the process), (d) shared Understanding (shared understanding) , (e) Intermediate Outcomes (interim final results). This research method uses a qualitative approach, a descriptive research method with qualitative analysis. Data collection techniques used in this research are observation, interviews and documentation. The research results show that Collaborative Governance in the Implementation of the Family Hope Program (PKH) in Tilamuta District, Boalemo Regency has been implemented, although the process is not yet optimal. This can be seen from the indicators of the collaboration process. Face to face dialogue has been carried out by agencies and stakeholders related to PKH, in the form of coordination meetings, outreach and other formal meetings. but this was not optimal because the meetings were not too intense. Building trust (Trust Building) has been built by relevant agencies and stakeholders, seen from the coordination and communication carried out by each party so that a sense of mutual trust is formed. (commitment to process) commitment in the collaboration process has been carried out by each party involved in implementing PKH, this can be seen from the coordination meeting where each party sat together to discuss solutions to resolve obstacles so that PKH runs effectively. (shared understanding) A common understanding has been carried out by the agencies and stakeholders involved in implementing PKH, even though each party has a different vision, in the collaborative process each party unites the goal for better PKH implementation, this can be seen from the coordination between parties. (intermediate outcomes) interim final results in the collaboration process carried out by agencies and other stakeholders have resulted in better cross-sector coordination and more accurate data integration. This synergy makes program monitoring easier and ensures that KPMs have optimal access to supporting services such as social and education. Penelitian ini bertujuan mengetahui dan mendiskripsikan Collaborative Governance dalam Implementasi Program Keluarga Harapan di Kecamatan Tilamuta Kabupaten Boalemo. Dilihat dari dimensi Collaborative Process: (a) Face to face dialogue (dialog tatap muka), (b) Trust Building (membangun kepercayaan), (c) Commitment to process (komitmen dalam proses), (d) shared Understanding (Pemahaman bersama), (e) Intermediate Outcomes (Hasil akhir sementara). Metode Penelitian ini menggunakan Pendekatan Kualitatif ini metode penelitian deskriptif dengan analisis kualitatif. Teknik Pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa Collaborative Governance dalam Implementasi Program Keluarga Harapan (PKH) di Kecamatan Tilamuta Kabupaten Boalemo telah di Implementasikan, meskipun prosesnya belum optimal. Hal ini dilihat dari indikator proses kolaborasi. dialog tatap muka (Face to face) telah dilakukan oleh Instansi dan Stakeholder terkait PKH, dalam bentuk rapat Koordinasi, sosialisasi dan pertemuan formal lainnya. tetapi hal ini belum optimal karena pertemuan yang dilakukan tidak terlalu intens. Membangun kepercayaan (Trust Building) telah dibangun oleh instansi dan stakeholder terkait, dilihat dari koordinasi dan komunikasi yang dilakukan oleh masing-masing pihak sehingganya terbentuknya rasa saling percaya. (commitmen to procces) komitmen dalam proses kolaborasi telah dilakukan oleh masing-masing pihak yang terlibat dalam implementasi PKH, hal ini dilihat rapat koordinasi yang dimana masing-masing pihak duduk bersama membahas solusi untuk menyelesaikan kendala agar PKH berjalan efketif. (shared understanding) Pemahaman bersama telah dilakukan oleh instansi dan stakeholder yang terlibat dalam pelaksanaan PKH, meskipun setiap pihak memiliki visi yang berbeda akan tetapi dalam proses kolaborasi setiap pihak menyatukan tujuan untuk pelaksaan PKH yang lebih baik, hal ini dilihat dari koordinasi antar pihak. (intermediate outcommes) hasil akhir sementara dalam proses kolaborasi yang telah dilakukan oleh instansi dan stakeholder lainnya telah menghasilkan koordinasi lintas sektor yang lebih baik dan integrasi data yang lebih akurat. Sinergi ini membuat pengawasan program lebih mudah dan memastikan KPM memiliki akses yang optimal ke layanan pendukung seperti sosial dan pendidikan.